Extraterritorial use of force against non-state actors - Lubell, Noam. (Oxford : Oxford University Press, 2010)
This text examines the legality of the use of force by states against individuals and non-state groups located beyond its borders, in light of applicable international law. The issues discussed include force used in the 'war on terror', pre-emptive self defence, and targeted killings of individuals.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Exterritoriality; Intervention (International law); Non-state actors (International relations); War (International law)